Parents' Mental and Emotional Disorders and Psychosocial Problems in Children at Public Elementary School 1 Kucur - Sunarto, Muhammad; Nova, Renny; Rosalina, Olivia Falla; Larasati, Indira Febiola (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
The psychosocial challenges faced by children may not always correspond with the emotional disorders exhibited by their parents. A robust support system from their social network can significantly contribute to the enhancement of their mental well-being. This study aims to investigate the relationship between parental emotional disorders and psychosocial issues in school-aged children. The research utilizes a descriptive correlational approach with a cross-sectional design, involving 165 students aged 6 to 12 from Public Elementary School 1 Kucur who are currently enrolled in school, along with one consenting parent, resulting in 330 respondents. The Self-Reporting Questionnaire-29 (SRQ-29) is used to identify parental emotional issues, while the Strengths and Difficulties Questionnaire (SDQ) assesses children's psychosocial problems. An analysis employing Somers' D Gamma was conducted to ascertain the correlation between parental mental-emotional disorders and children's psychological well-being. The findings reveal that the highest average score for parental mental-emotional disorders stands at 82.4%. In comparison, the highest average score for total difficulties in children's psychosocial issues is 58.8%, while the highest average prosocial score is 92.7%. The statistical analysis reveals no significant connection between parental emotional disorders and children's psychosocial problems on the prosocial scale (p=0.897) and total difficulties score (p=0.897). In conclusion, the findings of this research do not establish a direct link due to the numerous factors influencing children's psychosocial challenges.